2007
DOI: 10.4161/cc.6.21.4877
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gas1 in Embryonic Development and its Implications for Human Disease

Abstract: Growth arrest specific gene 1 (Gas1) has long been regarded as a cell cycle inhibitor of the G 0 to S phase transition. How GAS1, a GPI-anchored plasma membrane protein, directs intracellular changes without an extracellular ligand or a transmembrane protein partner has been puzzling. A recent series of biochemical and molecular genetic studies assigned the mammalian Hedgehog (HH) growth factor to be a ligand for GAS1 in vitro and in vivo. HH has enjoyed considerable attention for its profound role in embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 67 publications
2
53
0
Order By: Relevance
“…An analysis of Cdo, Boc and Gas1 mouse mutants confirms the importance of Cdo and Gas1 in the patterning of the ventral neural tube and points to the existence of functional compensation amongst these proteins (Allen et al, 2007;Martinelli and Fan, 2007;Tenzen et al, 2006). The onset of Cdo expression at the ventral midline of the neural tube occurs at the same time as floor plate specification (Fig.…”
Section: Extracellular Proteins Modulate Shh Spreadmentioning
confidence: 92%
See 2 more Smart Citations
“…An analysis of Cdo, Boc and Gas1 mouse mutants confirms the importance of Cdo and Gas1 in the patterning of the ventral neural tube and points to the existence of functional compensation amongst these proteins (Allen et al, 2007;Martinelli and Fan, 2007;Tenzen et al, 2006). The onset of Cdo expression at the ventral midline of the neural tube occurs at the same time as floor plate specification (Fig.…”
Section: Extracellular Proteins Modulate Shh Spreadmentioning
confidence: 92%
“…These include the related transmembrane proteins Cdo (also known as Cdon) and Boc, and the glycosylphosphatidylinositol (GPI)-linked protein Gas1 (Fig. 4) (Allen et al, 2007;Martinelli and Fan, 2007;Tenzen et al, 2006;Yao et al, 2006;Zhang et al, 2006). Surprisingly, their expression is generally, but not always, inhibited by Shh signaling.…”
Section: Extracellular Proteins Modulate Shh Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, one gene, Gas1, was markedly down-regulated (∼11-fold) in B16-F10 cells. Gas1 encodes a pleiotropic 45-kDa glycosylphosphatidylinositol-anchored membrane protein (Stebel et al 2000) that has been shown to play a role in both negative (Del Sal et al 1992;Lee et al 2001;Mellstrom et al 2002;Zamorano et al 2003Zamorano et al , 2004 and positive regulation of cell growth (Liu et al 2001;Spagnuolo et al 2004), as well as in embryonic development through regulation of Sonic Hedgehog signaling (for review, see Martinelli and Fan 2007b).…”
Section: Down-regulation Of Gas1 In B16-f10 Cells Contributes To Theimentioning
confidence: 99%
“…We have previously reported that microform HPE develops in growth arrest-specific gene 1 (Gas1) mutant mice (3,4). Additionally, we determined that the 37-kDa, cell surface-presented, and glycosylphosphatidylinositol-anchored GAS1 protein binds to the secreted cell-cell signaling protein Sonic hedgehog (SHH) and that it functions as a cell-autonomous enhancer of SHH signaling activity (3,5,6).…”
Section: Holoprosencephaly (Hpe)mentioning
confidence: 97%